Nanocrystalline cathode functional layer for SOFC. (20th January 2017) - Chrzan, Aleksander; Karczewski, Jakub; Szymczewska, Dagmara; Jasinski, Piotr
Abstract: Recently, it was shown that thin functional layers introduced between an electrolyte and cathode might improve cathode performance. However, the mechanism of this improvement still needs analysis. In this paper, a thin (∼140 nm), spin-coated perovskite layer (La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ ) was placed between a cathode (La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ ) and an electrolyte (Ce0.8 Gd0.2 O2-δ ) and the effects of this investigated. The microstructure of this layer was varied in order to determine its impact on the electrical and electrochemical properties. It has been shown that a mesoporous, nanocrystalline layer increases the active area for oxygen reduction and charge transfer through the cathode/electrolyte interface, which improves performance. Moreover, the stability of the cathode from thermal stresses is increased. In contrast, the coarsening of the grain and the layer densification has a reduced impact on the cathode performance.